Strategi Humas dalam Meningkatkan Kepercayaan Masyarakat pada PT. Pegadaian Kanwil 1 Medan - Cut Dhea Permata Sari; Siti Aisyah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This research uses a qualitative approach in data collection, where participant observation and in-depth interview techniques are used to gather information. The determination of informants was based on the Purposive Technique Sampling method, taking into account that the informants understood the situation and activities of PT Pegadaian Kanwil 1 Medan. The research results show that the image of PT Pegadaian Kanwil 1 Medan in society is formed through mass communication, group communication and interpersonal communication. Corporate Social Responsibility programs such as the Pegadaian Peduli Program and the Pegadaian Sharing Program are effective tools in fostering harmonious communication between companies and the community. This success in creating harmonious communication helps shape a positive image of the company in the community, which in turn can increase public trust in PT. Pegadaian Regional Office 1 Medan.